2004
DOI: 10.1111/j.1529-8817.2004.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

RECRUITMENT OF BENTHIC MICROCYSTIS (CYANOPHYCEAE) TO THE WATER COLUMN: INTERNAL BUOYANCY CHANGES OR RESUSPENSION?1

Abstract: In some lakes, large amounts of the potentially toxic cyanobacterium Microcystis overwinter in the sediment. This overwintering population might inoculate the water column in spring and promote the development of dense surface blooms of Microcystis during summer. In the Dutch Lake Volkerak, we found photochemically active Microcystis colonies in the sediment throughout the year. The most vital colonies originated from shallow sediments within the euphotic zone. We investigated whether recruitment of Microcysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 48 publications
9
116
0
Order By: Relevance
“…Compared to colonial Microcystis, the cell number of unicellular Microcystis had a significant decrease, suggesting that colonial Microcystis can survive a longer period under the stress of darkness and low temperature than unicellular Microcystis. This may be an explanation why Microcystis colonies were found in winter at the bottom of freshwater lakes (Reynolds et al, 1981;Tsujimura et al, 2000;Brunberg & Blomqvist, 2002;Latour et al, 2004a;Verspagen et al, 2004Verspagen et al, , 2005. Our previous study also indicated that colonial Microcystis exhibited more tolerance to copper than unicellular Microcystis (Wu et al, 2007), supporting that higher endurance to environmental stresses might play an important role in survivals of colonial Microcystis.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Compared to colonial Microcystis, the cell number of unicellular Microcystis had a significant decrease, suggesting that colonial Microcystis can survive a longer period under the stress of darkness and low temperature than unicellular Microcystis. This may be an explanation why Microcystis colonies were found in winter at the bottom of freshwater lakes (Reynolds et al, 1981;Tsujimura et al, 2000;Brunberg & Blomqvist, 2002;Latour et al, 2004a;Verspagen et al, 2004Verspagen et al, , 2005. Our previous study also indicated that colonial Microcystis exhibited more tolerance to copper than unicellular Microcystis (Wu et al, 2007), supporting that higher endurance to environmental stresses might play an important role in survivals of colonial Microcystis.…”
Section: Discussionmentioning
confidence: 49%
“…However, unlike some algae with capacity to form resting spores or stages (Anderson, 1976), cyst stages (Dale, 1983;Lewis et al, 1999), and akinetes (Li et al, 1997), Microcystis remains in a vegetative cell state at the sediment for the whole winter (Fallon & Brock, 1981;Reynolds et al, 1981;Tsujimura et al, 2000). Verspagen et al (2004) found that there were photochemically viable Microcystis cells in the water columns and sediments of Lake Volkerak throughout the year. Previous studies have been conducted by dealing with responses of Microcystis and other phytoplankton to only one factor of darkness or low temperature (Dehning & Tilzer, 1989;Furusato et al, 2004;Chu et al, 2007;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chemostats applied homogeneous mixing to single-celled Microcystis populations, whereas Microcystis often develops multicellular colonies migrating vertically in stagnant lakes (37). Microcystis is also known to survive prolonged burial in lake sediments, after which it can be resuspended in the water column (38). Both spatiotemporal heterogeneity and reseeding from the sediments tend to promote diversity, and may explain the observed co-occurrence of all three C i uptake genotypes in the lake.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, several factors could potentially drive such a vertical heterogeneity by influenc-ing the distribution of the colonies of M. aeruginosa into the water column: 1) interactions with the benthic compartment, by recruiting benthic colonies or by the continuous sedimentation of planktonic ones [29,40]; 2) vertical migration of the colonies, which can regulate their position in the water column by balancing their internal stock of gas vacuoles and carbon reserves [13,30,41,42]; and 3) fitness-related natural selection, which could allow some particular genotypes or phenotypes to better survive or develop at a specific depth because of particular conditions such as light intensity, nutrients availability or benefits of microcystin production [10,23,[43][44][45]. Since the qualitative shifts we observed were mainly restricted to the surface water layers of the deep reservoirs we studied, the influence of the interactions with the benthic compartment through recruitment or sedimentation can be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Many comprehensive studies have therefore been realized in order to explain the ecological success of this cyanobacterium and to unravel the complex set of factors driving both its dynamics and its toxicity. Such previous studies mainly dealt with the genetic diversity of M. aeruginosa's populations [4][5][6][7], the toxic potential of M. aeruginosa [8][9][10][11][12], and the determinism of the different steps of M. aeruginosa's life cycle [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%